The results of prospective multicenter study of the effectiveness of amino acid formula in infants with severe atopic dermatitis and allergy to cow's milk proteins - S.L. Nyankovskyy; O.G. Shadrin; V.A. Klimenko; D.O. Dobryanskyy; M.S. Iatsula; O.S. Ivakhnenko; S.M. Nedelska; T.V. Kobets; O.M. Ashcheulov; H.A. Haiduchyk; O.P. Paholchuk; O.V. Hostishcheva (Zaslavsky O.Yu., 2014)
The article presents the main results of prospective multicenter study of effectiveness of using amino acid formula in diet therapy for the infants with severe atopic dermatitis (AD) and allergy to cow's milk protein (CMP). The study was conducted in 5 centers of Ukraine and included 30 infants with severe atopic dermatitis (EASI score > 18) aged from 29 days to 11 months. 22 patients completed the study. Diet therapy considered administration of amino acid formula containing 100 % free amino acids, for 4 weeks. Evaluation of clinical effectiveness of AD and allergy to CMP diet therapy with amino acid formula was carried out on the 7th, 14th and 28th day after reaching the full daily volume of the formula. Provocative test was performed on the 28th day with extensively hydrolyzed whey protein formula followed with evaluation of immediate and late reactions. Infants with severe AD (EASI score > 18) were characterized by impairment of several organs and systems: in 68 % of cases skin symptoms were associated with the gastrointestinal signs like change in stool frequency (constipation, diarrhea), appearance of pathological admixtures in feces (mucus, blood), vomiting, and others. With administration of amino acid formula significant decrease in severity of skin (98 %) and gastro-intestinal manifestations of food allergy (82 %) were seen. Amino acid formula was well tolerated by children with severe AD and, if needed, it might be used as a therapeutic formula for an exclusive feeding of infants with severe allergies to CMP. Duration of the diet therapy should not be less than 4 weeks. High effectiveness of this formula in infants with AD was proved by parents and doctors.